Classroom assignment and social cohesion: Why ethnic origin and gender of students should be considered together - Clemens Kroneberg; Hanno Kruse; Andreas Wimmer (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Assigning students to school classes is a regular task for school administrators. With current practices focusing on equal class sizes, a balanced sex ratio, and pre-existing ties between students, schools miss out on a fundamental sociological insight: that social cohesion tends to benefit when students' socio-demographic attributes crisscross each other. Using survey data on school classes in four European countries, we study how the degree to which ethnic and gender boundaries align with each other affects students' friendships and identities. Our results show that, when classmates of different ethnic origins tend to be also of the opposite sex, minority students will have few inter-ethnic friendships and end up identifying less as members of the nation.
Keywords: 330